Relationship between career decision-making and parental career related behaviours among students of a private higher educational institution in Malaysia - Wong, Kah Yee; Zakaria, Noor Syamilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
In the past two decades, vocational development theories have been developed and established. One of the hallmarks of career counselling research involved investigation of the individual’s career decision-making process. Many career and career development theories are developed from the West, which its society culture foregrounded on individualistic; and previous research activities unserved on personal aptitudes, personalities, and values, which dearth in cultural diversity awareness. Malaysian culture diverged and rooted on collectivism. As such, Malaysian career counsellors need to be acquainted with clients who may have differences in culture background with the West. Thus, it was pivotal for career counsellors to take account of clients’ cultures, interests, values, capabilities, and their worldviews prior to render career counselling services. The purpose of this study deemed to investigate the relationship between career decision-making and parental career related behaviours among students at a private higher educational institute in Malaysia. This study aimed to investigate parental career related behaviours in students’ career decision-making process, as well as to identify and contrast the differences in gender toward parental career related-behaviors. In this study, Career Decision Self-Efficacy Scale-Short Form (CDSE-SF) and Parent Career Behavior Checklist were two instruments utilized. Finally, the null hypothesis of relationship between parental influences and career decision were accepted as well as a significant different in perceived parental influences between gender was found.